Concentration of Ammonium from Dilute Aqueous Solutions using Commercially Available Reverse Osmosis Membranes - Awobusuyi, Tolulope David (Université d'Ottawa / University of Ottawa, 2016)
Several commercially available reverse osmosis (RO) membranes were characterized with aqueous solutions of ammonium sulfate, potassium triphosphate, and mixtures of these two salts at different feed concentrations, compositions and pressures. The objective of this study was to investigate the rejection of these solutes, in particular the ammonium ion (NH4+), by different RO membranes. The aqueous solutions were assumed to come from an anaerobic digester via a process, currently under investigation by CHFour Biogas Inc., to maintain low concentrations of ammonia in the digester in order to maximize the biogas production. The ammonium ions present in the liquid produced from the process are then concentrated using membrane separation. The concentrated ammonium solution would be a valuable fertilizer that could be used by agriculture. The membranes were characterized with three models: the solution-diffusion model, the Kedem-Katchalsky model, also known as the irreversible thermodynamics model, and the Donnan Steric Pore Model (DSPM). The solution-diffusion and irreversible thermodynamics models were found to be inadequate for proper membrane characterization and the use of the DSPM model yielded membrane properties in good agreement with those found in already existing literature. The pore radius of investigated membranes ranged from 0.39 to 0.51 nm. The effect of pH on membrane surface charge was also studied, with the conclusion that increases in pH led to increasingly negative surface charges. This affected the transport of individual ions through the membrane due to preferential passage of the counter-ions. The effects of applied pressure on the stoichiometric nature of salt rejections were also studied. The minimal observed rejection from the range of experiments carried out using ammonium sulfate was 93%Non-stoichiometric rejections of ions were also observed in the experiments with single and multiple solutes. Furthermore, the rejection of ammonium ions in the presence of other ions (K+, SO42-, PO43-) increased as feed concentration increased, which was a result of the synergistic effects of feed pH and ionic interactions. The minimum NH4+ rejection in the presence of other ions was 95.4%, which suitability using RO membranes for concentration of ammonium from dilute aqueous solutions.
Keywords: Reverse Osmosis; Membrane Separation; Anaerobic digestion; Donnan steric pore model; Membrane characterization